CEMIP promotes extracellular matrix‐detached prostate cancer cell survival by inhibiting ferroptosis. Issue 6 (15th April 2022) - Liu, Bing; Li, Xuexiang; Wang, Decai; Yu, Ying; Lu, Dingheng; Chen, Liang; Lv, Fang; Li, Yunxue; Cheng, Lulin; Song, Yarong; Xing, Yifei
Abstract: Cells detached from the extracellular matrix (ECM) can trigger different modes of cell death, and the survival of ECM‐detached cells is one of the prerequisites for the metastatic cascade. Ferroptosis, a form of iron‐dependent programmed cell death, has recently been found to be involved in matrix‐detached cancer cells. However, the molecular mechanisms by which ECM‐detached cells escape ferroptosis are not fully understood. Here, we observed that cell migration‐inducing protein (CEMIP) upregulation facilitates ferroptosis resistance during ECM detachment by promoting cystine uptake in prostate cancer (PCa) cells. Meanwhile, silencing CEMIP causes it to lose its ability to promote cystine uptake and inhibit ferroptosis. Mechanistically, the interaction of CEMIP with inositol 1, 4, 5‐trisphosphate receptor type 3 (ITPR3) modulates calcium ion (Ca 2+ ) leakage from the endoplasmic reticulum, activating calcium/calmodulin‐dependent protein kinase II (CaMKII), which further facilitates nuclear factor erythroid 2‐related factor 2 (NRF2) phosphorylation and nuclear localization, leading to elevated transcription of solute carrier family 7 member 11 (SLC7A11), a glutamate/cystine antiporter, in PCa cells. Our findings delineate a novel role of CEMIP in ferroptosis resistance during ECM detachment and provide new insights into therapeutic strategies for metastatic PCa. Abstract : Ferroptosis was triggered by ECM detachment in prostate cancer cells, while the survival cells presented a ferroptosis‐resistant phenotype. Suppressing CEMIP expression led to detached cell death by boosting ferroptosis through inhibiting the ITPR3/CaMKII/NRF2/SLC7A11 pathway.